Menulis Masa Depan : Transformasi Pola Pikir Perilaku Seksual Pranikah Remaja - Miksa Denola Dusatri; Deby Amanda Putri; M. Lutfan Rais; Nuzul Khaira (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research examines the effectiveness of mentoring through writing letters to oneself in changing the mindset and premarital sexual behavior of adolescents. The subjects consisted of 60 students from two public universities in Bukittinggi. The research employed a quantitative method, specifically an experiment with a one-group pretest-posttest design. Adolescents wrote letters containing plans and commitments related to healthy sexual behavior. Data were collected through pretest and posttest questionnaires using a premarital sexual behavior scale. Paired Samples T-Test analysis results showed a significant difference between the mindset and premarital sexual behavior scores before and after the intervention (t = 14.061, df = 28, p < .001). These findings indicate that mentoring through writing letters to oneself is effective in changing the mindset and premarital sexual behavior of adolescents.